Pengaruh Integritas dan Karakteristik Individu terhadap Kinerja Pegawai pada Kantor Kecamatan Pasaribu Tobing Kabupaten Tapanuli Tengah - Richardo Sihombing; Rosmita Ambarita; Azriadi Tanjung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of Integrity and Individual Characteristics on Employee Performance at the Pasaribu Tobing Subdistrict Office, Central Tapanuli Regency. This research uses a quantitative descriptive method to describe and analyze the relationships between variables. The population in this study consisted of 30 employees, all of whom were used as the sample through a saturated sampling technique. The data used were primary data collected through questionnaires. The results of the instrument test indicate that all statement items for the variables of Integrity (X1), Individual Characteristics (X2), and Employee Performance (Y) are valid and reliable, with Corrected Item-Total Correlation values greater than 0.300 and Cronbach’s Alpha values greater than 0.60. The classical assumption tests show that the data are normally distributed and free from multicollinearity, heteroscedasticity, and autocorrelation, indicating that the regression model is appropriate. The results of data analysis show that partially, Integrity and Individual Characteristics have a positive and significant effect on Employee Performance. Simultaneously, both independent variables also have a significant effect on Employee Performance, with a coefficient of determination of 64.6%. This means that Integrity and Individual Characteristics explain 64.6% of the variation in Employee Performance, while the remaining 35.4% is influenced by other variables not examined in this study.